The importance of philosophical thinking in nursing science - Taevika Choakprasanchai; Amar Akbar (INTERNATIONAL JOURNAL OF NURSING AND MIDWIFERY SCIENCE (IJNMS), 2019)
In nursing field, point of view a nurse’s action on a patient, family, or community is as meaning of philosophy. Nevertheless, how does philosophy of science relate to nursing?, it is also a question that many people still doubt. This short essay aims to express my understanding about the importance philosophy of science and nursing science.Regarding to nursing field, why nursing have to concern itself with science is an important question. As we know, nurse’s role is to take care a patient and science is a way to build the knowledge.Philosophy of science and nursing science are so important, especially for nurses. It helps nurses to find out the reality of the truth and raise awareness of not only the uses scientific method to build the knowledge, but also applying the art in order to better taking care patient. Moreover, having deep understanding of philosophy, science, and nursing science is essential condition to become a nurse scientist to improve the best care practice.